MAV-ISR: from maritime gray zone competition to norm formation - Chen, Linlin (Frontiers in Marine Science, 2025)
Maritime Autonomous Vehicles-based Intelligence, Surveillance, and Reconnaissance (MAV-ISR) possesses unique and novel characteristics that distinguish it from other marine activities, providing a stark contrast with the uncertainty of its standing in international law. This ambiguity has resulted in different theoretical interpretations and practical concerns. In the South China Sea, conflicts of interest and practical confrontation between countries within and outside the region have given rise to a competitive gray zone, threatening the stability of the area. To mitigate the potential impact of the MAV-ISR gray zone on the international order, it is necessary to subject it to multidimensional evaluation. Normalizing MAV-ISR is the most thorough method for curbing its gray zone; however, this process should not be rushed. Its advancement should be a gradual process informed by a range of established methods and programs.